DOK3 Modulates Bone Remodeling by Negatively Regulating Osteoclastogenesis and Positively Regulating Osteoblastogenesis() - Cai, Xiaofeng (J Bone Miner Res, 2017)
Osteoclastogenesis is essential for bone remodeling and normal skeletal maintenance. RANKL promotes osteoclast differentiation and function but requires costimulation of immunoreceptor tyrosine-based activation motif (ITAM)-coupled immunoreceptors. Triggering receptor expressed on myeloid cells-2 (TREM2) coupled to ITAM-adaptor protein DNAX activation protein 12kDA (DAP12) provides costimulation of intracellular calcium signaling during osteoclastogenesis. Previously, we found that downstream of kinase-3 (DOK3) physically associates with DAP12 to inhibit toll-like receptor (TLR)-induced inflammatory signaling in macrophages. However, whether and how DOK3 modulates DAP12-dependent osteoclastogenesis is unknown and the focus of this study. Bone micro-architecture and histology of sex and age matched WT and DOK3-deficient (DOK3(-/-)) mice were evaluated. Male and female DOK3(-/-) mice have significantly reduced trabecular bone mass compared to WT mice with increased TRAP+ osteoclasts in vivo. In vitro, DOK3(-/-) BMMs have increased M-CSF induced proliferation and increased sensitivity to RANKL-induced osteoclastogenesis. Compared to WT, DOK3(-/-) osteoclasts are significantly larger with more nuclei and have increased resorptive capacity. Mechanistically, DOK3 limits osteoclastogenesis by inhibiting activation of Syk and ERK in response to RANKL and M-CSF. DOK3 is phosphorylated in a DAP12-dependent manner and associates with Grb2 and Cbl. Compared to DAP12(-/-) mice with high bone mass, DOK3- and DAP12- doubly deficient mice (DKO) have normalized bone mass, indicating that DOK3 also limits DAP12-independent osteoclastogenesis in vivo. In vitro osteoclasts derived from DKO mice are mononuclear with poor resorptive capacity similar to DAP12(-/-) osteoclasts. Histomorphometry reveals that DOK3(-/)(-) mice also have reduced osteoblast parameters. DOK3(-/-) osteoblasts have reduced in vitro osteoblastogenesis and increased OPG to RANKL expression ratio compared to WT osteoblasts. Co-culture of WT and DOK3(-/-) osteoblasts with pre-osteoclasts reveals a reduced capacity of DOK3(-/-) osteoblasts to support osteoclastogenesis. These data indicate that DOK3 regulates bone remodeling by negatively regulating M-CSF and RANKL mediated osteoclastogenesis and positively regulating osteoblastogenesis.